Faktor-Faktor Yang Berhubungan dengan Kejadian ISPA Pada Usia 0-4 Tahun di Puskesmas Kecamatan Tambora - Fatimah, Siti; Nitami, Mayumi; Mustikawati, Intan Silviana; Veronika, Erna (Mahesa Research Center, 2024)
Based on data from the Tambora District Health Center from 2021-2023, it shows an increase in ISPA cases at ages 0-4 years from 49.5%, 57.2%, 58.8%. The aim of this study was to determine the factors associated with the incidence of ARI at the age of 0-4 years at the Tambora District Health Center. This research used a Cross Sectional design with a sample of 66 respondents. Data analysis used univariate and bivariate analysis with the Chi Square test. The results of univariate analysis showed that more people experienced ARI (71.2%), mothers with low education (51.5%), age at risk (89.3%), not exclusively breastfed (57.6%), incomplete immunization ( 53%), nutritional status with normal body weight (68.2%), risky family smoking behavior (71.2%). There is a relationship between the incidence of ARI at the age of 0-4 years with maternal education (PR=1.824, 95% CI: 1.270-2.619), exclusive breastfeeding (PR=1.927, 95% CI: 1.276-2.911), immunization status (PR= 1.890, 95% CI: 1.295-2.756). Meanwhile, variables that did not have a relationship between the incidence of ARI were age under five (PR=1.275, 95% CI: 0.659-2.468), nutritional status and family smoking behavior (PR=1.179, 95% CI: 0.805-1.728).